Republic of Moldova : Technical Assistance Report-Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance Report on the Republic of Moldova provides details of IMF mission to review available source data for deposit takers and other sectors including other financial corporations (OFCs); and to review the current financial soundness indicators (FSI) compiled by the National Bank of Moldova with a view to ensure methodological consistency of the FSI compilation with the IMF's FSI Compilation Guide 2006. The mission found some deviations from the FSI Guide in key indicators currently compiled based on the International Financial Reporting Standards and Basel III principles as well as national supervisory standards. Some methodological deviations include the measurement of capital. In order to support progress in the above work areas, the mission recommended a detailed action plan with several priority recommendations. It is recommended to expand the coverage of the OFCs sector to include the non-bank credit organizations (microfinance institutions and leasing companies) in collaboration and coordination with the National Commission for Financial Markets.